:NALISIS KINERJA SISTEM INSTALASI PENGOLAHAN LUMPUR TINJA KOTA MAGELANG - Sudarno, Sudarno (Universitas Diponegoro, 2006)
Domestic wastewater treatment was needed for every towns. This domestic wastewater such black water and grey water shouldÂ be treated for not poltuted the environment. Magelang was on of town which has have domestic treatment plant with capacity of 20,5m3/dayThis plantÂ was done by Dinas PengendalianÂ Lingkungan Hidup. It had many several series treatment unit consisted of equalizing basin unit, anaerobic lagoon, facultative lagoon maturation lagoon and sludge drying bed. Further more, after having all of treatment steps, the treated efftuent could safely discharged to sufface water bodies without causing poltution problem